Cross-cultural, population-based study on adolescent body image and eating distress in Japan and Finland - Maezono J.; Hamada S.; Sillanmäki L.; Kaneko H.; Ogura M.; Lempinen L.; Sourander A. (Blackwell Publishing Ltd, 2022)
This cross‐sectional population‐based survey compares the prevalence of self‐reported body image and eating distress symptoms among adolescents in Japan and Finland, and associations between emotional/behavioral problems, body image and eating distress from a cross‐cultural perspective. The study included 1,840 Japanese and 1,135 Finnish 8th grade students. The self‐reported questionnaire included the Body Image and Eating Distress Scale and Strengths and Difficulties Questionnaire (SDQ). The female adolescents from both Finland and Japan reported much greater dissatisfaction with, and concern about, their bodies than the males and Japanese females expressed even higher distress than Finnish females. High levels of body image and eating distress were associated with psychiatric problems measured with the SDQ. There was a significant three‐way interaction effect of body image and eating distress, gender and country with SDQ peer problems and prosocial behavior.